The Mapping of Usrah Rabbani KIAS Module and Its Importance In Strengthening Students' Self-Identity - Rahim Kamarul Zaman; Mujiburrahman Muhammad Saleh; Nur Shahidah Ab Hamid; Khairol Mokhtar; Siti Nur Fatin Jaafar (Rabbanica: Journal of Revealed Knowledge)
The development of human identity through the formal education system is part of the main indicator of the civilization of a country. Thus, a comprehensive and sustainable education system and curriculum structure are very important. In the Islamic tradition, usrah is among the educational methods that are often used as a complement to formal education to develop a student's self-identity. In this context, various variations of usrah methods have developed worldwide following current needs. Accordingly, this study is presented to discuss the Usrah Rabbani method that has been practiced as a mechanism for strengthening the self-identity of students at Sultan Ismail Petra International Islamic University College (KIAS). As an Islamic Higher Education Institution under the Kelantan State Government, the Usrah Rabbani method has been developed in parallel with the Kelantan Rabbani Education Policy (DPRK) to produce a generation of Rabbani. Based on the method of textual analysis, this study found that the Usrah Rabbani curriculum contains 91 Nas al-Quran discourses, 23 hadith topics, 16 Islamic History topics and 11 Islamic thought topics. Overall, this study found that the curriculum combination of the Usrah Rabbani method is very relevant to the need to strengthen the identity of today's students. Therefore, the Usrah Rabbani method based on the DPRK deserves to be recognized as one of the best models in the context of student self-identity development at the higher education institution level.